Implementasi Program Jasa Layanan Netra (JANETA) Mobile Unit di UPT Rehabilitasi Sosial Bina Netra Malang Dinas Sosial Provinsi Jawa Timur - Pratiwi, Adellia Mega; Prabawati, Indah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Public services are a fundamental aspect of fulfilling citizens' basic rights, including those of vulnerable groups such as individuals with visual impairments. However, limited access to inclusive social services remains a significant challenge for them. In response to this issue, the East Java Provincial Social Service launched the Jasa Layanan Netra (JANETA) Mobile Unit program, aimed at providing mobile-based social rehabilitation services for visually impaired individuals in Malang City and Malang Regency. This study seeks to analyze the implementation of the JANETA Mobile Unit program at the UPT Rehabilitasi Sosial Bina Netra Malang using Edward III’s implementation theory, which focuses on four key aspects: communication, resources, disposition, and bureaucratic structure. This research employs a qualitative descriptive method through in-depth interviews, direct observation, and document analysis. The findings indicate that the JANETA Mobile Unit program has had a positive impact on individuals with visual impairments, particularly in enhancing their Braille reading skills, mobility orientation, and independent living abilities. However, several challenges persist, including insufficient budget allocations for maintaining facilities and infrastructure, as well as a lack of public awareness, which has led to stigmatization of the program’s implementation. In conclusion, while the JANETA Mobile Unit program has significantly improved access to social rehabilitation services for visually impaired individuals, further improvements are necessary in communication, resource management, and cross-sector collaboration. Therefore, this study recommends increasing budget allocations, expanding public outreach efforts, and strengthening cooperation among stakeholders to ensure the program’s sustainability and effectiveness.